Ideal Model of Gorontalo Regional Land Asset Management to Prevent Disputes and Ensure Legal Certainty - Julia Kristi Karepoan; Zamroni Abdussamad; Erman I. Rahim (Jurnal Hukum Prasada, 2026)
Regional property (BMD) plays a strategic role in governance and fulfilling constitutional rights, yet in Gorontalo province, land assets frequently become dispute objects, threatening governance stability and development. This study critically analyzes BMD land asset management regulations within the legislative hierarchy and formulates an ideal dispute prevention model based on good governance principles. Using a juridical-normative method with statutory, conceptual, and case approaches examining disputes over Djalaluddin Airport and the Student Education and Training Center, plus BPK audit results the research reveals that current regulations remain administrative and fragmentary. They fail to mandate binding deadlines for land certification, require integrated databases between local governments and BPN, or establish preventive asset audits as security instruments, enabling recurring, costly disputes. This article proposes a four-pillar model: mandatory certification with deadlines, a digital Integrated Asset Information System, annual preventive audits, and massive legal counseling. Normatively compatible with existing laws, this model offers practical potential to reduce disputes, ensure legal certainty, and optimize regional land asset utilization.